The portrayals of state machinery figures in combating COVID-19 in Malaysia : a study on Ernest Ng’s CovidBall Z - Nazima Versay Kudus,; Noor Azli Affendy Lee, (Penerbit Universiti Kebangsaan Malaysia, 2022)
In this time of pandemic, people engage with diverse narratives of infographics to make sense of their experiences. Scholars agreed that comics are graphic mediums and cultural artefacts that significantly contribute to the visual community of the COVID-19 pandemic. One of the comic artists in Malaysia, Ernest Ng, initially published his comics online and later converted them into three volumes of comic books entitled CovidBall Z Volume 1 (2020a), 2 (2020b) and 3 (2021). The objective of this paper is to undertake a content analysis of the portrayals of the various state machinery figures both from the government and opposition sides (i.e., ministers, politicians and government officers) in their roles in combating COVID-19. Additionally, the analysis wishes to uncover contemporary attitudes Ng uses such as symbolism, exaggeration and irony, among others, to convey his views on the current issue in obvious and subtle ways. In analysing the data, this study employed data analysis techniques in the form of descriptive content analysis. It was found that the social commentaries presented in Ng’s comics via the plot depict the existence of sexism, unfair treatment, and prejudice by several characters which lead to bully culture in the midst of the political metaphorical depiction of war and heroism among Malaysian state machinery figures. The images in his comics help people analyse, reflect on, and interpret our experiences by informing, providing meaning, and illustrating the COVID-19 outbreak narrative.